DOI: 10.51415/10321/3188
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of Western Cape ALS providers to provide clinical stabilisation and intensive care for neonates during the patient journey

Abstract: The management and intensive care of neonates is inherently prone to adverse events, particularly as such management often involves pre-term neonates in distress – this means they have been born too early and their frail bodies require external support in order to survive. In the Western Cape high-risk neonates who are being referred from one neonatal intensive care unit (NICU) to another such unit or from primary and secondary hospitals to NICU are transported by ALS providers. However, there is a paucity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The need for additional education in neonatal CCR was described by the prospective student group. This result was also reported by Ismail et al [11] in a descriptive study where ALS providers from the Western Cape, South Africa felt that they require additional exposure and training in neonatal transfers. The same result was also reported by Ashokcoomar et al [22] in a descriptive study where seven neonatologists from the state sector in South Africa indicated that ALS providers who transfer neonates require specialised education.…”
Section: Plos Onesupporting
confidence: 82%
See 4 more Smart Citations
“…The need for additional education in neonatal CCR was described by the prospective student group. This result was also reported by Ismail et al [11] in a descriptive study where ALS providers from the Western Cape, South Africa felt that they require additional exposure and training in neonatal transfers. The same result was also reported by Ashokcoomar et al [22] in a descriptive study where seven neonatologists from the state sector in South Africa indicated that ALS providers who transfer neonates require specialised education.…”
Section: Plos Onesupporting
confidence: 82%
“…10 Apply and analyse a variety of methods used for the monitoring of a critical neonate during retrieval and transport. 11 Describe the physiological effects that the different modes of transport could have on the neonate and apply methods to mitigate potential risks to the neonatal patient during transport. 12 Describe and demonstrate the monitoring, care and management of a variety of ventilation modes and methods as they relate to neonatal critical care and transport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations